MANAJEMEN KURIKULUM INTRAKURIKULER PADA PROGRAM DESAIN KOMUNIKASI VISUAL DALAM MEMBANGUN LITERASI DIGITAL DI SEKOLAH MENENGAH KEJURUAN NEGERI 5 JEMBER - Zulfa Hoirin Nisa; Nur Ittihadatul Ummah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the process of intracurricular curriculum management, which refers to the management of the curriculum implemented during official school hours to support the achievement of effective learning objectives, particularly in strengthening students' competencies in specific fields. The Visual Communication Design (DKV) program at SMK Negeri 5 Jember serves as a creative learning medium based on technology that is relevant for developing digital literacy. Digital literacy itself is the ability to understand, use, and utilize technology and digital media wisely and productively.